Atypical root resorptions and impact of early deciduous tooth loss: a clinical case report (Research, Society and Development, 2022)
The root resorption of deciduous teeth is characterized by the loss of part of the tooth structure and is determined physiologically by the eruption of the successor tooth or pathologically by external or internal injury. It affects the cementum, dentin, and sometimes even the alveolar bone. The atypia seen in root resorption can derive from an inflammatory process subsequent to trauma or caused by pressure from some injurious agent, such as an ectopic erupting tooth, and almost invariably complicate the chronology and sequence of normal eruption. Early losses of deciduous teeth usually generate problems in clinical practice, allowing arch length reduction, inclinations and rotations of the succeeding tooth and its neighbors. The aim of this article is to report a case of early tooth 75 loss due to external root resorption followed by infection and pulp necrosis as a consequence of tooth 34 eruption, as well as to briefly discuss ectopic eruptions and the impact of early deciduous tooth loss. Based on the case report and discussion, it is concluded that it is necessary that dental surgeons have knowledge about atypical root resorption and be qualified for early diagnosis and appropriate intervention. It is also understood that further studies on the condition are needed for a better understanding of the pathophysiological mechanisms involved in these root resorptions that deviate from the physiological pattern